2010
DOI: 10.1016/j.dld.2010.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of hepatitis C treatment in Southern Italy

Abstract: a b s t r a c tBackground: Only a small proportion of subjects referring to hospitals for hepatitis C virus (HCV) positivity receives antiviral therapy. Aim: To evaluate the rate of antiviral treatment and the causes for no treatment in HCV-RNA positive subjects seen in hospital settings. Patients and methods: A prospective study enrolling over a 6-month period (February-July 2009) all consecutive anti-HCV positive subjects initially referred (naïve patients) to 12 liver units in Southern Italy for HCV treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
0
12
0
3
Order By: Relevance
“…Recently, we have evaluated the effectiveness of hepatitis C virus (HCV) treatment in Southern Italy [5]. It has allowed us a good opportunity to evaluate in the same area even the current practice of HBV infection treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have evaluated the effectiveness of hepatitis C virus (HCV) treatment in Southern Italy [5]. It has allowed us a good opportunity to evaluate in the same area even the current practice of HBV infection treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 469 studies were identified, of which 454 were captured by the search strategy and 15 by hand searching. The inclusion criteria were fulfilled in 25 studies , from which data were extracted and analysed. The studies flow is shown in Figure .…”
Section: Studies Flowmentioning
confidence: 99%
“…Included studies were heterogeneous, with a variety of designs and aims. The vast majority of studies were from Western Europe (22/25 or 88%) , of which six were from France and six from Italy . Two studies were from Eastern Europe and one pan‐European .…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations